2012
DOI: 10.1002/gea.21389
|View full text |Cite
|
Sign up to set email alerts
|

Obsidian Subsource Identification in the Sierra de Pachuca and Otumba Volcanic Regions, Central Mexico, by ICPMS and DBSCAN Statistical Analysis

Abstract: Otumba and Sierra de Pachuca obsidian deposits in Central Mexico have been important sources of raw material since pre‐Hispanic times. Numerous archaeological investigations have suggested that the economical and political expansion of major Mesoamerican societies were linked to the control of obsidian sources and distribution of quarried material. Sierra de Pachuca contains several obsidian flows and numerous quarries throughout the region that were preferentially exploited by different cultures. The Otumba V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Studies of Mesoamerican obsidian sources have identified spatially and geochemically distinct variation at major sources such as Pachuca (Glascock ; Argote‐Espino et al . ), Otumba (Argote‐Espino et al . ) and Zaragoza‐Oyameles (Knight et al .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Mesoamerican obsidian sources have identified spatially and geochemically distinct variation at major sources such as Pachuca (Glascock ; Argote‐Espino et al . ), Otumba (Argote‐Espino et al . ) and Zaragoza‐Oyameles (Knight et al .…”
Section: Introductionmentioning
confidence: 99%
“…We found that all the artifacts assigned to the Sierra de Pachuca source group corresponded to green obsidian samples, without overlapping with any of the other groups. The Sierra de Pachuca is a well-known geological source renowned for its valuable green translucent volcanic glass [41,[44][45][46]. The grouping was also evaluated by means of a contingency table (Table 3), whose rows are the sources groups and the columns the result of the clustering.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that larger sample sizes generate more complex overlapping, making group discrimination more difficult. The only groups with a clear separation from the other are Sierra de Pachuca and El Pizarrín-Tulancingo; this can be explained by the distinctive greater concentrations of zirconium and zinc of these sources compared to other regional deposits [44][45]. Zinapecuaro and Zacualtipan also show a wide dispersion of the data points, not forming compact groups.…”
Section: A Comparison To Conventional Clustering and Pca Projectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we summarize the elemental, isotopic, and geochronological exploratory research into successful discrimination of these important Southwestern sources of archaeological obsidian in order to provide a database and strategy to deal with this problem, one that is present in other volcanic provinces worldwide (e.g., Argote‐Espino, Solé, López‐Garcia, & Stepone, ; Brown, Reid, & Negash, ; Chataigner & Gratuze, ; Glascock, ; Morgan, Renne, Taylor, & WoldeGabriel, ; Poidevin, ; Poupeau et al., ; Sahle, Morgan, Braun, Atnafu, & Hutchings, ; Shackley & Sahle, ; Vogel, Nomade, Negash, & Renne, ; Weisler & Woodhead, ). In order to provide clarity beyond XRF, we have acquired Sr, Pb, and Nd isotopic data along with 40 Ar/ 39 Ar ages from sample splits for these sources (see Supplementary Document 1 for laboratory and instrumental methods for XRF, the isotopic analysis, and 40 Ar/ 39 Ar dating).…”
Section: Introductionmentioning
confidence: 99%